Development of an immobilization system for in situ micronutrients release - Ramos, Philippe Emmanuel Cruz (2016)
An immobilization system constituted by coated microcapsules was developed aiming at immobilizing probiotic bacteria capable of producing folate and release it in a sustained manner into the intestine. Despite no probiotic folate-producers have been immobilized so far, the system has been developed with this goal and this work reports its stability and ability to release folate under gastro-intestinal conditions. Microcapsules were made of alginate with three consecutive coatings of poly-l-lysine, sodium alginate and chitosan. Turbidity experiments showed a strong electrostatic interaction between these polymers. Fourier transform infrared spectroscopy (FTIR) and confocal analysis showed the stability of the coating materials when applied on the microcapsules, even after they were immersed in solutions simulating conditions in the stomach and small intestine (i.e. pH 2, 60 min and pH 7.2, 120 min, respectively). Coated microcapsules have an average diameter size ranged from 20 and 40 ?m, and swelled upon exposure to a neutral medium, without dissolution as showed by microscopy analyses. Release experiments proved the ability of the coated microcapsules to release folic acid, at different rates, depending on the applied coating. Release experiments showed that the first coating (?-PLL) is characterized by Fickian diffusion as the main release mechanism of folic acid. Fickian rate constant (kF) decreased with the number of consequent coatings, reflecting the decrease of predominance of Fick's behavior. Results showed that the developed coated microcapsules have suitable characteristics for encapsulation of folic acid aiming in situ release in the intestine.